ANALISIS KEBUTUHAN IMPLEMENTASI PROJECT BASED LEARNING TERINTEGRASI CULTURALLY RESPONSIVE TEACHING PADA PENINGKATAN HASIL BELAJAR MATERI BIOTEKNOLOGI KONVENSIONAL - Aulia Zaldiana; Yayuk Mulyati; Aulia Zaldiana (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
The aim of this research is to find solutions to improve student learning outcomes based on everyday cultural context problems. Various studies reveal that lacking problem solving skills will make learning less meaningful and result in low student learning outcomes. This is also known from the lack of student involvement due to monotonous learning activities so that students tend to get bored and bored. The method used is literature review and interviews aimed at teachers learning conventional biotechnology. Based on the literature review of interviews conducted, an ideal solution was obtained to solve this problem, namely the application of Project Based Learning with a Culturally Responsive Teaching approach to improving learning outcomes in Conventional Biotechnology. To be able to produce a product that is a solution, students start from a problem that refers to the context of cultural introduction, namely poisoning of tapai fermented processed products. Providing authentic project-based learning has an impact on developing internal motivation, creativity, a sense of responsibility, cooperation and problem solving abilities as a result of projects carried out to produce maximum results.